2015
DOI: 10.1021/acs.joc.5b01764
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting thegem-Disubstitution Effect in FcPHOX and HetPHOX P,N Ligands: Synthesis and Applications in Pd-Catalyzed Intermolecular Heck Reactions

Abstract: The synthesis of a range of novel gem-disubstituted and electronically varied thiophene-oxazoline (HetPHOX) ligands and ferrocene-oxazoline (FcPHOX) ligands and their application in the Pd-catalyzed intermolecular asymmetric Heck reaction (IAH) is described. These investigations show that gem-disubstitution of i-Pr-PHOX-type ligands can lead to effective and cost-efficient alternatives to the corresponding t-Bu-PHOX systems. The Pd complexes of these ligands were very effective in the IAH, providing phenylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Palladium‐catalyzed Heck reaction of 2,3‐dihydrofuran and phenyl triflate was then tested with L17 as a ligand, which delivered the desired product in 94% ee with 98% conversion (Scheme 19). [ 26 ] Moreover, as shown in Scheme 20, enantioselective Heck reactions of 5‐substituted‐2,3‐dihydrofurans with aryl triflates were independently developed by Hou and Ding, and Mazet, which afforded optically active 2,3‐ or 2,5‐dihydrofurans containing C2‐tetrasubstituted all‐carbon stereocenters in excellent ee values with moderate to excellent yields by using ( R )‐SDP(O), pyridine‐phosphine L18 , or ( S )‐Diflurophos as chiral ligands. [ 27 ] It was observed that olefin isomerization of the Heck product could be remarkably inhibited in the presence of ( R )‐SDP(O) ligand.…”
Section: Palladium‐catalyzed Intermolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…Palladium‐catalyzed Heck reaction of 2,3‐dihydrofuran and phenyl triflate was then tested with L17 as a ligand, which delivered the desired product in 94% ee with 98% conversion (Scheme 19). [ 26 ] Moreover, as shown in Scheme 20, enantioselective Heck reactions of 5‐substituted‐2,3‐dihydrofurans with aryl triflates were independently developed by Hou and Ding, and Mazet, which afforded optically active 2,3‐ or 2,5‐dihydrofurans containing C2‐tetrasubstituted all‐carbon stereocenters in excellent ee values with moderate to excellent yields by using ( R )‐SDP(O), pyridine‐phosphine L18 , or ( S )‐Diflurophos as chiral ligands. [ 27 ] It was observed that olefin isomerization of the Heck product could be remarkably inhibited in the presence of ( R )‐SDP(O) ligand.…”
Section: Palladium‐catalyzed Intermolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…The complex derived from ligand 1a was of the type PdCl 2 (PHOX) and crystallized as monomer 5b exhibiting a 5 C 2 conformation of the pyranose ring instead of a 2 C 5 conformation as depicted in 5a (Scheme , Figure ). The formation of complexes of the type PdCl 2 (PHOX) is common for PHOX ligands and there are some examples of similar complexes with other PHOX ligands in the literature . The pivaloyl protected ligand 1e afforded the complex 6c which crystallized as a dimeric complex of the type [PdCl 2 (PHOX)] 2 (Scheme , Figure ) with the sugar in a 2 C 5 conformation.…”
Section: Resultsmentioning
confidence: 97%
“…In an attempt to achieve higher selectivity, we examined the use of the 4-isopropyl-5,5-dimethyloxazoline group [ 18 , 19 ]. Reaction of the amino alcohol with the acid chloride derived from 47 led to the hydroxy amide 55 ( Scheme 11 ).…”
Section: Resultsmentioning
confidence: 99%